Repeated low-level red-light therapy vs. conventional treatments for myopic control in children: a systematic review and meta-analysis - Li Ping Liu; Yi Shan Hu; Huai Cheng Chen; Yun Tang; Xiao Min Mao (Scientific Reports)
Abstract This meta-analysis aimed to evaluate the effectiveness of repeated low-level red-light (RLRL) therapy compared to conventional myopia treatments to guide clinical application. A comprehensive literature search was conducted using PubMed, Embase, Web of Science, and Cochrane Library databases from their inception to December 2024. To quantify changes in axial length (AL), we computed weighted mean differences (WMDs) with 95% confidence intervals (CIs). Meta-regression and subgroup analyses were used to explore heterogeneity based on intervention duration and treatment type, while publication bias and result stability were assessed using Egger’s and Begg’s tests and sensitivity analysis, respectively. Seven studies, comprising one non-randomized controlled trial, two cohort studies, and four randomized controlled trials, were included, involving 691 pediatric participants (349 in the RLRL group and 342 in the control group receiving orthokeratology and atropine). Overall, AL progression in the RLRL group was significantly lower than in the control group (WMD=–0.24 mm, 95% CI [–0.33, − 0.14], P < 0.001, I2 = 93.5%), with benefits increasing over time. At the same time, we also found that the effect of RLRL adjunctive therapy (WMD=–0.35 mm, 95% CI = [–0.46, − 0.24]) in controlling axial length growth was better than that of monotherapy (WMD=–0.19 mm, 95% CI = [–0.28, − 0.10]). Moreover, RLRL demonstrated a notable enhancement in choroidal thickness, surpassing the effects observed with both orthokeratology (OK) lenses and 0.01% atropine treatments (WMD = 30.79 μm, 95% CI = [17.28, 44.30], I2 = 72.7%, P < 0.05). The reported data from the included studies demonstrated the absence of serious adverse events. RLRL therapy may slow myopia progression more effectively than current standard treatments, but further well-designed trials with longer follow-ups are needed to confirm its clinical value.